On Parallel Software Verification using Boolean Equation Systems - Ditter, Alexander; Ceska, Milan; Lüttgen, Gerald (Lecture Notes in Computer Science, 2012)
Multi- and many-core hardware platforms are today widely accessible and used to significantly accelerate many computationally demanding tasks. In this paper we describe a parallel approach to solve Boolean Equation Systems (BESs) in the context of model checking. We focus on the applicability of state-of-the-art, shared-memory parallel hardware - multi-core CPUs and many-core GPUs - to speed up the resolution procedure for BESs. In this setting, we experimentally show the scalability and competitiveness of our approach, compared to an optimized sequential implementation, based on a large benchmark suite containing models of software systems and protocols from industry and academi
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD3.onpara
Keywords: boolean equation systems; formal verification; parallel model checking